2010
DOI: 10.1177/0145482x1010401010
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Opportunities: A Study of Children with Cortical Visual Impairment

Abstract: PediatricView is an evaluation project that began in 1999 and is located at Western Pennsylvania Hospital in Pittsburgh. It is affiliated with the hospital's Department of Pediatrics and Neonatology and was initiated as an adjunct to the neonatal developmental follow-up clinic. The purpose of Pediatric View is to provide developmental and functional vision evaluations to children who have ocular or cortical visual impairments. A team that includes a neonatologist and an individual who has expertise in child de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Some studies have reported that the CVI phases and scoring system can be used to guide visual therapy and monitor treatment response. 15 , 19 , 45 However, it has also been stated that further research and evidence are needed to support the role of this scoring system in the clinic. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that the CVI phases and scoring system can be used to guide visual therapy and monitor treatment response. 15 , 19 , 45 However, it has also been stated that further research and evidence are needed to support the role of this scoring system in the clinic. 11 …”
Section: Discussionmentioning
confidence: 99%
“…The Cortical Visual Impairment Range Assessment (CVIRA) [ 33 ] is a reliable functional vision assessment designed to investigate the visual characteristics associated with CVI. It measures the degree of CVI severity on a 0–10 continuum where 0 represents no visual function and 10 represents near typical visual function [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Roman-Lantzy scale has been designed for the assessment of visual and behavioral characteristics in terms of color preference, visual latency, need for movement, difficulty with novelty, visual field preferences, complexity (array, objects, faces, and sensory environment), difficulty with distance viewing, need for light, atypical visual reflexes, and difficulty with visually guided reach in children with CVI is most commonly used for the evaluation of functional vision in these children. [ 15 ]…”
Section: Clinical Evaluationmentioning
confidence: 99%